Replacement of a Phosphoenolpyruvate-dependent Phosphotransferase by a Nicotinamide Adenine Dinucleotide-linked Dehydrogenase for the Utilization of Mannitol - Tanaka, Shuji (1967)
Mannitol is dissimilated by Aerobacter aerogenes via an inducible pathway initiated by a phosphotransferase system dependent upon phosphoenolpyruvate as the phosphoryl donor. A mutational block in this pathway can be suppressed either at the phenotypic level by induction of d-arabitol dehydrogenase, an enzyme fortuitously capable of converting mannitol to fructose, or genotypically by a constitutive mutation in the d-arabitol system.